A house with good bones eaudiobook - Kingfisher, T. (Macmillan Audio, 2023)
"...splendidly performed by Mary Robinette Kowal." - AudioFile Magazine "Narrator Mary Robinette Kowal wonderfully conveys the wryly funny prose and the creeping horror of the story. Giving each character a distinct voice, Kowal deftly and consistently moves between them and superbly renders Sam's voice."- Library Journal A haunting Southern Gothic from an award-winning master of suspense, A House With Good Bones explores the dark, twisted roots lurking just beneath the veneer of a perfect home and family. "Mom seems off." Her brother's words echo in Sam Montgomery's ear as she turns onto the quiet North Carolina street where their mother lives alone. She brushes the thought away as she climbs the front steps. Sam's excited for this rare extended visit, and looking forward to nights with just the two of them, drinking boxed wine, watching murder mystery shows, and guessing who the killer is long before the characters figure it out. But stepping inside, she quickly realizes home isn't what it used to be. Gone is the warm, cluttered charm her mom is known for; now the walls are painted a sterile white. Her mom jumps at the smallest noises and looks over her shoulder even when she's the only person in the room. And when Sam steps out back to clear her head, she finds a jar of teeth hidden beneath the magazine-worthy rose bushes, and vultures are circling the garden from above. To find out what's got her mom so frightened in her own home, Sam will go digging for the truth. But some secrets are better left buried. Also by T. Kingfisher Nettle & Bone What Moves the Dead A Macmillan Audio production from Tor Nightfire.